Estimation of sink capacity of rice grains: A comparison of calculation methods based on 1000-grain weight and grain projected area - Masaki Okamura; Ryutaro Morita; Yumiko Arai-Sanoh; Hiroe Yoshida; Hiroshi Nakagawa; Naohiro Aoki (Plant Production Science, 2023)
ABSTRACTAccurate estimation of sink capacity in rice (grain number × potential grain size), independent of grain filling, is necessary for considering source – sink interactions. However, how to measure potential grain size is still a matter of debate. Here, we investigated the effect of modifying the grain-filling environment on 1000-grain weight of grains screened by specific gravity or brown rice thickness, grain projected area (‘grain area’), or husk weight as candidate indicators of potential grain size using a japonica cultivar Koshihikari and its near-isogenic line with greater spikelet number. We found grain area to be the best, followed by 1000-grain weight. We developed a novel method to calculate sink capacity from grain area; the method was developed based on the relationship between individual grain weight and grain area. Comparison with the conventional method based on 1000-grain weight showed that although the method based on grain area is more accurate, that based on 1000-grain weight is useful enough, because screening by specific gravity or brown rice thickness selected filled grains well, and the effect of the grain-filling environment on 1000-grain weight was limited.